"الذات" في أدب إقبال مفهومها، ومعالم بنائها، ودورها في النهوض الحضاري للأمة - محمد أعظم الندوي (International Institute of Islamic Thought, 2016)
تعالج هذه الورقة موضوع الذات في كتابات إقبال: من حيث مفهومها، ومعالم بنائها، ودورها في النهوض الحضاري للأمة، وذلك بتحليل كلمة "خودي" أو الذات، وأثبتت أن إقبال أراد بالذات معرفة النفس، وتعيين الذات، وأن هذه الفكرة هي أساس فكره، وأنه استقى فكرته هذه من القرآن الكريم، والتصوّف الإسلامي، ومع ذلك يوجد تشابه نوعي بين فكره وأفكار الفلاسفة الألمان، ومن ذلك فكرة أن كل موجودات الكون تحمل ذاتاً تهتمّ بها، والذات الإنسانية تفوقها بمواهبها الابتكارية، وعوامل قوتها. وعندما تجتمع ذوات بهذه المواهب والعوامل يتكون المجتمع المثالي، وهذا يتطلب احترام الآخرين، وهذا ما سماه إقبال بنفي الذات. وأظهرت الورقة قدرة فكرة الذات على إنشاء التكامل الفكري، والمعرفي، والنهوض بالأمة حضاريًّا، وأنها تركت أبعاداً واسعة في مجال الإصلاح، والتجديد الفكري. This paper investigates the topic of "Self or Ego" in Iqbal's writings: its concept, building features, and its role in the Umma cultural advancement, through analyzing the term khodi = self or ego. When Iqbal talks about self, he means self-knowledge and self-identification. The "self" idea is the basis of Iqbal's thought, were he drew it from the Holy Quran and Islamic Sufism. However we may find a similarity between his thought and thoughts and ideas of German philosophers, especially his idea that all existing things in the universe have an "ego" to care about, and human ego has a superiority due to its innovative talents ant to factors that increase its strength. When egos with such specifications meet, an ideal society is made up. This requires respect for others, and the demand to deny oneself. The paper shows the ability of the ego idea to create intellectual and epistemological integration, to help the Umman to achieve cultural advancement and to provide wide horizons in the field of reform and intellectual renewal.